Analysis and Design of High Gain NRI Superstrate Based Antenna for RF Energy Harvesting System - Ng, Ch (Telkomnika Indonesian Journal of Electrical Engineering, 2016)
A high gain patch antenna inspired by 4 layers of negative refractive index (NRI) metamaterial (MTM) superstrate is proposed to operate at downlink radio frequency (RF) band (935MHz to 960MHz) of GSM 900). The MTM unit cell consists of a nested split ring resonator (SRR) on one side and strip line laminated on other side of FR4 substrate. The effective permeability and permittivityof the unit cell are designed synchronously to approach zero, which leads the NRI superstrate to have impedance match with zero negative refractive index.The NRI superstrate is studied using Fabry-Perot (F-P) resonant cavity. The gain of the antennas is improved by 82.29% at the air gap of 55 mm in the desired frequency band. The gain is effectively enhanced based on the negative refractive index MTM. The measured radiation pattern and s parameter results showed that it has good agreement with the simulation results.